A glue-free three-layer solar back panel and preparation method thereof
Through the extrusion granulation process without glue and a combination of specific materials, the reduction of water vapor barrier rate and PID problems in existing solar backplanes are solved, better sealing performance and ultraviolet shielding effect are achieved, and the backplane is improved Strength and cold resistance.
Patent Information
- Application Number
- CN202210104213.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-28
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2042-01-28
AI Technical Summary
The water vapor barrier rate caused by polyester structure or adhesives in existing solar back panels is reduced, and ionic precipitation and migration caused by grafting materials exacerbate the PID problem of components.
The solar back panel is made of a glue-free three-layer structure, and the outer layer is the outer layer, the intermediate layer and the inner layer. The materials of each layer contain polypropylene, polyethylene, olefin-based elastomer and filler, and are prepared by extrusion granulation process. Avoid adhesive use, while introducing polyethylene grafts and microfibrillated cellulose to improve adhesion and UV shielding.
It achieves better sealing performance, PID resistance and UV shielding effect, while avoiding the use of adhesives, improving the strength and cold resistance of the backplate.
Smart Images

Figure BDA0003493309710000101
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solar modules, the IPC classification number of which is H01L31 / 0203, and in particular to a glue-free three-layer solar back sheet and a preparation method thereof. Background Art
[0002] The solar backsheet is located on the back of the solar panel and provides protection and support for it. The current solar backsheet has a multi-layer structure. The middle layer of the three-layer solar backsheet is generally a polyester structure or an adhesive layer prepared with other adhesives. However, the polyester structure or adhesive will reduce the water vapor barrier rate of the backsheet.
[0003] Patent CN107275429A provides an extruded solar backsheet, which adds grafted materials to improve the uniformity and interlayer adhesion of the product. It does not require an adhesive layer or a polyester structure. At the same time, after the backsheet is corona treated, the adhesion between the backsheet and the sealing silicone used in the solar cell sealing frame is increased, making the sealing performance better. However, the addition of grafted materials causes ion precipitation and migration in the glass, exacerbating the PID of the component. Summary of the invention
[0004] In order to solve the above technical problems, a first aspect of the present invention provides a glue-free three-layer solar back panel, which includes an outer layer, a middle layer, and an inner layer from the outside to the inside.
[0005] The thickness of the outer layer is 100-300 μm.
[0006] The thickness of the intermediate layer is 10-100 μm.
[0007] The thickness of the inner layer is 200-500 μm.
[0008] The raw materials of the outer layer include, by weight, 70-90 parts of polypropylene, 10-20 parts of metallocene ethylene-hexene copolymer, 15-30 parts of filler and 0-3 parts of additive.
[0009] The raw materials of the middle layer include, by weight, 70-90 parts of polypropylene, 8-15 parts of polyethylene, 5-10 parts of fillers, 5-10 parts of olefin-based elastomer (POE), and 0-3 parts of additives.
[0010] The raw materials of the inner layer include, by weight, 50-60 parts of polypropylene, 50-60 parts of polyethylene, 5-10 parts of polyethylene grafts, 5-10 parts of fillers and 0-3 parts of additives.
[0011] In some preferred embodiments, the raw materials for the outer layer include, by weight, 80 parts of polypropylene, 15 parts of metallocene ethylene-hexene copolymer, 22 parts of fillers, and 1.5 parts of additives; the raw materials for the middle layer include, by weight, 80 parts of polypropylene, 12 parts of polyethylene, 8 parts of fillers, 8 parts of POE, and 1.5 parts of additives; the raw materials for the inner layer include, by weight, 55 parts of polypropylene, 55 parts of polyethylene, 8 parts of polyethylene grafts, 8 parts of fillers, and 1.5 parts of additives.
[0012] Polypropylene
[0013] Polypropylene is a thermoplastic. According to the type of monomer, polypropylene is divided into homopolymer polypropylene, random copolymer polypropylene and block copolymer polypropylene.
[0014] As a preferred embodiment of the present invention, the polypropylene is a combination of homopolymer polypropylene and block copolymer polypropylene, and the weight ratio thereof is 1:(0.3-0.8), preferably 1:(0.4-0.6), and more preferably 1:0.5.
[0015] The homopolymer polypropylene has a melt index of 5 to 12 g / 10 min at 230° C. and 2.16 kg, such as Sanren F850EA (On-spec.) from Shanghai Petrochemical.
[0016] The block copolymer polypropylene has a melt index of 4 to 9 g / 10 min at 230° C. and 2.16 kg, such as Sanren M700R (On-spec.) from Shanghai Petrochemical.
[0017] Polyethylene
[0018] The polyethylene is obtained by addition polymerization of ethylene, and the polyethylene is selected from one or more of low-density polyethylene, linear low-density polyethylene, medium-density polyethylene, high-density polyethylene, and ultra-high molecular chain polyethylene.
[0019] Preferably, the polyethylene is a linear low-density polyethylene. More preferably, the linear low-density polyethylene has a melt index of 0.6 to 2 g / 10 min (preferably 1 g / 10 min) at 190°C and 2.16 kg, for example, a linear low-density polyethylene of model TAISOX 2410.
[0020] Polyethylene graft
[0021] The polyethylene graft is a maleic anhydride or acrylic polyethylene graft. Preferably, the polyethylene graft is a maleic anhydride polyethylene graft.
[0022] Maleic anhydride polyethylene grafts are obtained by grafting several maleic anhydride molecules onto polyethylene molecular chains through some chemical reactions. The maleic anhydride polyethylene grafts have a melt index of 0.1 to 0.5 g / 10 min (preferably 0.3 g / 10 min) at 190°C and 2.16 kg. For example, the brand name ADMER TM Maleic anhydride grafted polyethylene of AT2235E.
[0023] Olefin-based elastomer (POE)
[0024] The olefin-based elastomer (POE) of the present invention is composed of repeating monomers of isotactic polypropylene and randomly distributed ethylene. The melt index of the POE at 190°C and 2.16 kg is 2 to 5 g / 10 min. The POE can be obtained from the market, for example, the model is Vistamaxx. TM 3980FL POE (melt index is 3.2g / 10min at 190°C and 2.16kg).
[0025] In the present invention, polyethylene grafts are introduced into the middle layer and the inner layer, so that the compatibility and dispersibility of the raw materials in the system are better, and the adhesion between the layers is increased. At the same time, the polyethylene grafts and microfibrillated cellulose also give the inner layer a certain polarity, which can be well bonded with the EVA adhesive layer. The solar module prepared using the back panel can also be well bonded to the frame, which better improves the sealing performance of the module.
[0026] filler
[0027] The filler is a combination of hydrotalcite, cerium phosphate and microfibrillated cellulose, and the weight ratio thereof is (8-12):(4-6):(2.5-4), preferably 10:5:3.
[0028] The hydrotalcite is magnesium aluminum hydrotalcite.
[0029] The microfibrillated cellulose has an aspect ratio of 2 to 20 (preferably 8 to 15) and a length of 1000 to 1500 nm.
[0030] In the present invention, the filler is mixed and pulverized to an average particle size of less than 100 μm before use.
[0031] Titanium dioxide is often used in the prior art to achieve the effect of ultraviolet shielding, but its main anti-ultraviolet area is the UVA band, and the ultraviolet protection degree for the UVB band is relatively low. There is an electronic transition between the electronic orbit of the phosphate ion and the electronic orbit of the cerium ion in cerium phosphate, which makes it have good ultraviolet absorption, but it may be because the structure of the single cerium phosphate is a rod-like structure, which is easy to agglomerate in the system, and its ultraviolet absorption effect is not good when used alone. The applicant unexpectedly found that the synergistic effect between the use of hydrotalcite and microfibrillated cellulose in the present invention can better increase the ultraviolet shielding effect of the backboard, which may be because microfibrillated cellulose has a certain long diameter and hydrotalcite has a layered structure. The dispersibility of cerium phosphate is increased in the system under the synergistic effect of the two. At the same time, the special long diameter structure of microfibrillated cellulose makes the charge migration number of the system large, so that adding a large amount of cerium phosphate can achieve a better ultraviolet shielding effect.
[0032] Metallocene ethylene-hexene copolymer
[0033] The melt index of the metallocene ethylene-hexene copolymer at 190°C and 2.16kg is less than 5g / 10min (for example, less than 4g / 10min, less than 3g / 10min, less than 2g / 10min, less than 1g / 10min, less than 0.6g / 10min, less than 0.3g / 10min or 0.6-2g / 10min). The sales brands include Exceed TM 1015HA.
[0034] Although the addition of microfibrillated cellulose can increase the UV shielding effect of the backboard, it will reduce the water vapor barrier property of the backboard to a certain extent. The applicant unexpectedly discovered that the addition of hydrotalcite in the present invention can not only increase the water vapor barrier property of the backboard, but it may be because the alkyl in the system, especially the hydrophobic alkyl of the metallocene ethylene-hexene copolymer, can increase the interlaminar spacing between the hydrotalcites during the processing, and better extend the path for the water vapor molecules to pass through. At the same time, the long alkyl chains of the system can be modified on the surface of the hydrotalcite and the microfibrillated fibers, reducing the free volume of the system. In addition, the hydrotalcite has certain ion exchange properties. The metallocene ethylene-hexene copolymer and the polyethylene graft are interlaced between two adjacent anions during the processing, which is similar to the effect of intramolecular hydrogen bonds, further enhancing the UV absorption capacity.
[0035] additive
[0036] The additive is at least one of an antioxidant, an ultraviolet absorber, and a light stabilizer.
[0037] Examples of antioxidants include antioxidant 264, antioxidant DNP, antioxidant 168, and the like.
[0038] Examples of the ultraviolet absorber include ultraviolet absorber RMB, ultraviolet absorber UV-P, ultraviolet absorber UV-9, and the like.
[0039] Examples of light stabilizers include light stabilizer 770, light stabilizer 292, light stabilizer 944, light stabilizer 3853, etc.
[0040] A second aspect of the present invention provides a method for preparing a glue-free three-layer solar backsheet, comprising the following steps:
[0041] (1) stirring and mixing the materials of the outer layer according to the above weight parts at a speed of 500 to 1000 rpm to obtain a premix, conveying the prepared premix to a granulation extruder for extrusion granulation at 180 to 240° C. to obtain granules A for standby use;
[0042] (2) stirring and mixing the materials of the middle layer according to the above weight parts at a speed of 500 to 1000 rpm to obtain a premix, conveying the prepared premix to a granulation extruder for extrusion granulation at 180 to 240° C. to obtain granules B for standby use;
[0043] (3) stirring and mixing the materials of the inner layer according to the above weight parts at a speed of 500 to 1000 rpm to obtain a premix, conveying the prepared premix to a granulation extruder for extrusion granulation at 180 to 240° C. to obtain granules C for standby use;
[0044] (4) The prepared pellets A, B and C are respectively conveyed to the co-extrusion backplane production line extruders A, B and C, and after melting and plasticization, are extruded through a common rectangular die to obtain a sheet melt; the sheet melt is cooled and shaped by a cooling roller, and is rolled or cut into sheets to obtain the glue-free three-layer solar backplane.
[0045] The present invention has at least the following beneficial effects:
[0046] 1. The solar backsheet needs to have a certain support function during use. The use of homopolymer polypropylene in the present invention makes the solar backsheet have better strength. At the same time, adding a certain amount of block copolymer polypropylene improves the defect of poor impact resistance of homopolymer polypropylene to a certain extent;
[0047] 2. The use of polyethylene and block copolymer polypropylene in the present invention can not only better improve the defect of poor impact resistance of homopolymer polypropylene, but also select linear low-density polyethylene to improve the defect of poor cold resistance of polypropylene, so that the solar backsheet has not only good strength but also good cold resistance;
[0048] 3. Through a large number of research and development tests, it is found that the selection of polyolefins with a specific melt index in the present invention enables better compatibility between different polymerized olefins and better processing performance during processing;
[0049] 4. Although maleic anhydride polyethylene grafts are added in the present invention, the solar backsheet still has good PID resistance, which may be because the specific fillers used in the present invention have a special layered structure and physical and chemical properties that prevent the dissociation of ions, thereby reducing the carriers in the backsheet;
[0050] 5. The glue-free three-layer solar back sheet of the present invention avoids the use of adhesives and has good bonding properties between the layers. DETAILED DESCRIPTION
[0051] Example 1
[0052] A glue-free three-layer solar back sheet, comprising an outer layer, a middle layer, and an inner layer from the outside to the inside; the thickness of the outer layer is 10 μm; the thickness of the middle layer is 300 μm; the thickness of the inner layer is 30 μm;
[0053] The raw materials of the outer layer include, by weight, 70 parts of polypropylene, 10 parts of metallocene ethylene-hexene copolymer, 15 parts of fillers, and 1 part of additives; the raw materials of the middle layer include, by weight, 70 parts of polypropylene, 8 parts of polyethylene, 5 parts of fillers, 5 parts of POE, and 1 part of additives; the raw materials of the inner layer include, by weight, 50 parts of polypropylene, 50 parts of polyethylene, 5 parts of polyethylene grafts, 5 parts of fillers, and 1 part of additives;
[0054] The polypropylene is a combination of homopolymer polypropylene and block copolymer polypropylene, and the weight ratio thereof is 1:0.4;
[0055] The homopolymer polypropylene is Sanren F850EA (On-spec.) of Shanghai Petrochemical, with a melt index of 8.5 g / 10 min at 230°C and 2.16 kg; the block copolymer polypropylene is Sanren M700R (On-spec.) of Shanghai Petrochemical, with a melt index of 6.5 g / 10 min at 230°C and 2.16 kg;
[0056] The polyethylene is a linear low-density polyethylene; the model of the linear low-density polyethylene is TAISOX 2410, and the melt index is 1 g / 10 min at 190° C. and 2.16 kg;
[0057] The polyethylene grafted product is a maleic anhydride polyethylene grafted product; the brands of maleic anhydride polyethylene grafted products include ADMER TMAT2235E, melt index at 190°C, 2.16kg is 0.3g / 10min;
[0058] The POE model is Vistamaxx TM 3980FL, melt index at 190°C, 2.16kg is 3.2g / 10min;
[0059] The filler is a combination of hydrotalcite, cerium phosphate and microfibrillated cellulose, with a weight ratio of 8:4:2.5; the hydrotalcite is magnesium aluminum hydrotalcite; the microfibrillated cellulose has an aspect ratio of 8 and a length of 1000 nm; the filler is mixed and crushed to an average particle size of less than 100 μm before use;
[0060] Metallocene ethylene-hexene copolymers are sold under the brand name Exceed TM 1015HA, melt index at 190°C, 2.16kg is 1g / 10min;
[0061] The additive is a combination of antioxidant 264 and ultraviolet absorber RMB, and the weight ratio thereof is 1:1;
[0062] The method for preparing the glue-free three-layer solar back sheet comprises the following steps: (1) stirring and mixing the materials of the outer layer according to the above weight portions at a rotation speed of 500 rpm to obtain a premix, conveying the prepared premix to a granulation extruder for extrusion granulation at 190° C. to obtain granules A for standby use; (2) stirring and mixing the materials of the middle layer according to the above weight portions at a rotation speed of 500 rpm to obtain a premix, conveying the prepared premix to a granulation extruder for extrusion granulation at 190° C. to obtain granules B for standby use; (3 ) The materials of the inner layer are stirred and mixed at a speed of 500 rpm according to the above weight portions to obtain a premix, and the prepared premix is conveyed to a granulation extruder for extrusion granulation at 190° C. to obtain granules C for standby use; (4) The prepared granules A, B, and C are conveyed to co-extrusion backplane production line extruder A, extruder B, and extruder C respectively, and after melting and plasticization, they are extruded through a common rectangular die to obtain a sheet melt; the sheet melt is cooled and shaped by a cooling roller, and is rolled or cut into sheets to obtain the glue-free three-layer solar backplane.
[0063] Example 2
[0064] A glue-free three-layer solar back sheet, comprising an outer layer, a middle layer, and an inner layer from the outside to the inside; the thickness of the outer layer is 50 μm; the thickness of the middle layer is 200 μm; the thickness of the inner layer is 50 μm;
[0065] The raw materials of the outer layer include, by weight, 90 parts of polypropylene, 20 parts of metallocene ethylene-hexene copolymer, 30 parts of fillers, and 3 parts of additives; the raw materials of the middle layer include, by weight, 90 parts of polypropylene, 15 parts of polyethylene, 10 parts of fillers, 10 parts of POE, and 3 parts of additives; the raw materials of the inner layer include, by weight, 60 parts of polypropylene, 60 parts of polyethylene, 10 parts of polyethylene grafts, 10 parts of fillers, and 3 parts of additives;
[0066] The polypropylene is a combination of homopolymer polypropylene and block copolymer polypropylene, with a weight ratio of 1:0.6;
[0067] The homopolymer polypropylene is Sanren F850EA (On-spec.) of Shanghai Petrochemical, with a melt index of 8.5 g / 10 min at 230°C and 2.16 kg; the block copolymer polypropylene is Sanren M700R (On-spec.) of Shanghai Petrochemical, with a melt index of 6.5 g / 10 min at 230°C and 2.16 kg;
[0068] The polyethylene is a linear low-density polyethylene; the model of the linear low-density polyethylene is TAISOX 2410, and the melt index is 1 g / 10 min at 190° C. and 2.16 kg;
[0069] The polyethylene grafted product is a maleic anhydride polyethylene grafted product; the brands of maleic anhydride polyethylene grafted products include ADMER TM AT2235E, melt index at 190°C, 2.16kg is 0.3g / 10min;
[0070] The POE model is Vistamaxx TM 3980FL, melt index at 190°C, 2.16kg is 3.2g / 10min;
[0071] The filler is a combination of hydrotalcite, cerium phosphate and microfibrillated cellulose, with a weight ratio of 12:6:4; the hydrotalcite is magnesium aluminum hydrotalcite; the microfibrillated cellulose has an aspect ratio of 15 and a length of 1500nm; the filler is mixed and crushed to an average particle size of less than 100μm before use;
[0072] Metallocene ethylene-hexene copolymers are sold under the brand name Exceed TM 1015HA, melt index at 190°C, 2.16kg is 1g / 10min;
[0073] The additive is a combination of antioxidant 168, ultraviolet absorber RMB, and light stabilizer 292, and the weight ratio thereof is 1:1:1;
[0074] The method for preparing the glue-free three-layer solar back sheet comprises the following steps:
[0075] (1) The materials of the outer layer were stirred and mixed at a speed of 1000 rpm according to the above weight portions to obtain a premix, and the prepared premix was conveyed to a granulation extruder for extrusion granulation at 230° C. to obtain granules A for standby use; (2) The materials of the middle layer were stirred and mixed at a speed of 1000 rpm according to the above weight portions to obtain a premix, and the prepared premix was conveyed to a granulation extruder for extrusion granulation at 230° C. to obtain granules B for standby use; (3) The materials of the inner layer were stirred and mixed at a speed of 1000 rpm according to the above weight portions to obtain a premix, and the prepared premix was conveyed to a granulation extruder for extrusion granulation at 230° C. to obtain granules B for standby use; The materials are stirred and mixed at a speed of 1000 rpm to obtain a premix, and the prepared premix is conveyed to a granulation extruder for extrusion granulation at 230° C. to obtain granules C for standby use; (4) the prepared granules A, B, and C are conveyed to co-extrusion backplane production line extruder A, extruder B, and extruder C respectively, and after melting and plasticization, they are extruded through a common rectangular die to obtain a sheet melt; the sheet melt is cooled and shaped by a cooling roller, and is rolled or cut into sheets to obtain the glue-free three-layer solar backplane.
[0076] Example 3
[0077] A glue-free three-layer solar back sheet, comprising an outer layer, a middle layer, and an inner layer from the outside to the inside; the thickness of the outer layer is 50 μm; the thickness of the middle layer is 300 μm; the thickness of the inner layer is 50 μm;
[0078] The raw materials of the outer layer include, by weight, 80 parts of polypropylene, 15 parts of metallocene ethylene-hexene copolymer, 22 parts of fillers, and 1.5 parts of additives; the raw materials of the middle layer include, by weight, 80 parts of polypropylene, 12 parts of polyethylene, 8 parts of fillers, 8 parts of POE, and 1.5 parts of additives; the raw materials of the inner layer include, by weight, 55 parts of polypropylene, 55 parts of polyethylene, 8 parts of polyethylene grafts, 8 parts of fillers, and 1.5 parts of additives.
[0079] The polypropylene is a combination of homopolymer polypropylene and block copolymer polypropylene, and the weight ratio thereof is 1:0.5;
[0080] The homopolymer polypropylene is Sanren F850EA (On-spec.) of Shanghai Petrochemical, with a melt index of 8.5 g / 10 min at 230°C and 2.16 kg; the block copolymer polypropylene is Sanren M700R (On-spec.) of Shanghai Petrochemical, with a melt index of 6.5 g / 10 min at 230°C and 2.16 kg;
[0081] The polyethylene is a linear low-density polyethylene; the model of the linear low-density polyethylene is TAISOX 2410, and the melt index is 1 g / 10 min at 190° C. and 2.16 kg;
[0082] The polyethylene grafted product is a maleic anhydride polyethylene grafted product; the brands of maleic anhydride polyethylene grafted products include ADMER TM AT2235E, melt index at 190°C, 2.16kg is 0.3g / 10min;
[0083] The POE model is Vistamaxx TM 3980FL, melt index at 190°C, 2.16kg is 3.2g / 10min;
[0084] The filler is a combination of hydrotalcite, cerium phosphate and microfibrillated cellulose, with a weight ratio of 10:5:3; the hydrotalcite is magnesium aluminum hydrotalcite; the microfibrillated cellulose has an aspect ratio of 12 and a length of 1200 nm; the filler is mixed and crushed to an average particle size of less than 100 μm before use;
[0085] Metallocene ethylene-hexene copolymers are sold under the brand name Exceed TM 1015HA, melt index at 190°C, 2.16kg is 1g / 10min;
[0086] The additive is a combination of antioxidant 168, ultraviolet absorber RMB, and light stabilizer 292, and the weight ratio thereof is 1:1:1;
[0087] The method for preparing the glue-free three-layer solar back sheet comprises the following steps:
[0088] (1) The materials of the outer layer were stirred and mixed at a speed of 800 rpm according to the above weight portions to obtain a premix, and the prepared premix was conveyed to a granulation extruder for extrusion granulation at 210° C. to obtain granules A for standby use; (2) The materials of the middle layer were stirred and mixed at a speed of 800 rpm according to the above weight portions to obtain a premix, and the prepared premix was conveyed to a granulation extruder for extrusion granulation at 210° C. to obtain granules B for standby use; (3) The materials of the inner layer were stirred and mixed at a speed of 800 rpm according to the above weight portions to obtain a premix, and the prepared premix was conveyed to a granulation extruder for extrusion granulation at 210° C. to obtain granules B for standby use; The materials are stirred and mixed at a speed of 800 rpm to obtain a premix, and the prepared premix is conveyed to a granulation extruder for extrusion granulation at 210° C. to obtain granules C for standby use; (4) the prepared granules A, B, and C are conveyed to co-extrusion backplane production line extruder A, extruder B, and extruder C respectively, and after melting and plasticization, they are extruded through a common rectangular die to obtain a sheet melt; the sheet melt is cooled and shaped by a cooling roller, and is rolled or cut into sheets to obtain the glue-free three-layer solar backplane.
[0089] Example 4
[0090] A glue-free three-layer solar back panel, the specific implementation of which is the same as that of Example 3, except that the filler is titanium dioxide.
[0091] Example 5
[0092] A glue-free three-layer solar back sheet, the specific implementation of which is the same as that of Example 3, except that there is no hydrotalcite in the filler and no metallocene ethylene-hexene copolymer in the raw material of the outer layer.
[0093] Performance Testing
[0094] 1. UV aging resistance test
[0095] The elongation retention rate at break of the glue-free three-layer solar backsheet UV400KWh prepared according to IEC61215:2005ISO 527.3 test;
[0096] Evaluation criteria: A is when the elongation at break retention rate is greater than or equal to 400%; B is when the elongation at break retention rate is greater than or equal to 360% and less than 400%; C is when the elongation at break retention rate is greater than or equal to 320% and less than 360%; D is when the elongation at break retention rate is less than 320%.
[0097] 2. Electrical performance test
[0098] The test sample was prepared by placing the three-layer solar back panel of glass / EVA / cell / EVA / glue-free into a laminator for lamination (the lamination temperature was 140°C, the pressure was 0.1 MPa, and the time was 5 min), wherein the glass, EVA, and cell were from the same batch and model.
[0099] Test method: Test the PID 1000 power variation according to the method in IEC61215:2005.
[0100] Evaluation criteria: PID 1000 power change is less than or equal to 3.8%, which is A; PID 1000 power change is less than or equal to 5 and greater than 3.8%, which is B; PID 1000 power change is greater than 5%, which is C.
[0101] 3. Water vapor transmission rate
[0102] Test the water vapor transmission rate of glue-free three-layer solar backsheet according to ISO 15106-2.
[0103] Evaluation criteria: Water vapor transmission rate less than 0.8g / m 2 .d is A; water vapor transmission rate is less than or equal to 1.5g / m 2 .d. Greater than 0.8g / m2 .d, B; water vapor transmission rate is less than 2.5g / m 2 .d. Greater than 1.5g / m 2 .d, is C, water vapor transmission rate is greater than or equal to 2.5g / m 2 .d stands for D.
[0104] The test results are shown in Table 1:
[0105] Table 1
[0106]
Claims
1. A glue-free three-layer solar back sheet, comprising an outer layer, a middle layer, and an inner layer from the outside to the inside, characterized in that: The raw materials of the outer layer include, by weight, 70-90 parts of polypropylene, 10-20 parts of metallocene ethylene-hexene copolymer, 15-30 parts of fillers, and 0-3 parts of additives; the raw materials of the middle layer include, by weight, 70-90 parts of polypropylene, 8-15 parts of polyethylene, 5-10 parts of fillers, 5-10 parts of olefin-based elastomers, and 0-3 parts of additives; the raw materials of the inner layer include, by weight, 50-60 parts of polypropylene, 50-60 parts of polyethylene, 5-10 parts of polyethylene grafts, 5-10 parts of fillers, and 0-3 parts of additives; The filler is a combination of hydrotalcite, cerium phosphate and microfibrillated cellulose, and the weight ratio thereof is (8-12): (4-6): (2.5-4); the aspect ratio of the microfibrillated cellulose is 2-20, and the length is 1000-1500 nm; the average particle size of the filler is less than 100 μm; The metallocene ethylene-hexene copolymer has a melt index of less than 5 g / 10 min at 190° C. and 2.16 kg; The polypropylene is a combination of homopolymer polypropylene and block copolymer polypropylene, and the weight ratio thereof is 1:(0.3-0.8); the homopolymer polypropylene has a melt index of 5-12 g / 10 min at 230° C. and 2.16 kg; the block copolymer polypropylene has a melt index of 4-9 g / 10 min at 230° C. and 2.16 kg; The polyethylene is a linear low-density polyethylene, and the melt index is 0.6-2 g / 10 min at 190° C. and 2.16 kg; The polyethylene graft is a maleic anhydride polyethylene graft, and the melt index is 0.1-0.5 g / 10 min at 190° C. and 2.16 kg. The olefin elastomer is composed of repeating monomers of isotactic polypropylene and randomly distributed ethylene, and has a melt index of 2 to 5 g / 10 min at 190° C. and 2.16 kg. The additive is at least one of an antioxidant, an ultraviolet absorber, and a light stabilizer.
2. A method for preparing a glue-free three-layer solar backsheet according to claim 1, comprising the following steps: (1) Mixing the materials of the outer layer according to the above weight portions at a speed of 500 to 1000 rpm to obtain a premix, conveying the prepared premix to a granulation extruder for extrusion granulation at 180 to 240° C. to obtain granules A for standby use; (2) stirring and mixing the materials of the middle layer according to the above weight parts at a speed of 500 to 1000 rpm to obtain a premix, conveying the prepared premix to a granulation extruder for extrusion granulation at 180 to 240° C. to obtain granules B for standby use; (3) stirring and mixing the materials of the inner layer according to the above weight parts at a speed of 500 to 1000 rpm to obtain a premix, conveying the prepared premix to a granulation extruder for extrusion granulation at 180 to 240° C. to obtain granules C for standby use; (4) The prepared pellets A, B and C are respectively conveyed to the co-extrusion backplane production line extruders A, B and C, and after melting and plasticization, are extruded through a common rectangular die to obtain a sheet melt; the sheet melt is cooled and shaped by a cooling roller, and is rolled or cut into sheets to obtain the glue-free three-layer solar backplane.
Citation Information
Patent Citations
Extrusion type solar backboard and preparing method thereof
CN106279904A
Extrusion type solar energy backboard and manufacturing method thereof
CN107275429A
Compound for cold drawing sleeving film, and cold drawing sleeving film
CN110776689A
